2016
DOI: 10.22492/ije.4.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Metacognitive Awareness among the Foundation in Engineering Students

Abstract: The transition phase is a critical moment to students who have completed their secondary school education and are proceeding to pre-university education in Malaysia. The long duration of exposure to rote-learning and examination oriented education systems at school has somehow shaped these students' perceptions about teaching and learning. Thus, this paper aims to examine the quality of first year students' experiences in constructing their knowledge and skills throughout the Foundation in Engineering (FIE) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, the findings of Amzil and Stine-Marrow (2013) indicated that metacognitive knowledge is not a predictor of academic performance even though metacognitive monitoring and control are good predictors. Poh et al (2016) also found no relation between metacognitive awareness and the overall academic achievement of students.…”
Section: Resultsmentioning
confidence: 78%
“…However, the findings of Amzil and Stine-Marrow (2013) indicated that metacognitive knowledge is not a predictor of academic performance even though metacognitive monitoring and control are good predictors. Poh et al (2016) also found no relation between metacognitive awareness and the overall academic achievement of students.…”
Section: Resultsmentioning
confidence: 78%
“…In other words, what they know about declarative, procedural, and conditional knowledge (Baker, 1991) determines task performance (Filho & Yuzawa, 2001). On the other hand, metacognitive regulation, sometimes referred to as metacognitive skill (Flavell & Miller, 2002), is a more active process that applies metacognitive knowledge to the task at hand (Pintrich et al, 2000;Poh et al, 2016). Metacognitive knowledge includes awareness about the cognitive processes one uses to learn and remember (Ormrod & Davies, 2004).…”
Section: Metacognitionmentioning
confidence: 99%
“…Students thus had the opportunity to make their thinking about this critical topic visible, and at the same time, learn from the best strategies their peers are using. As noted by researchers in [6][7][8], awareness of metacognitive processes can help in ways of improving understanding of a topic. By deliberately discussing these and other learning strategies as part of in-class activities, students are encouraged to monitor their understanding as they read or apply it for working through technical scenarios.…”
Section: Critical Reading and Annotations In The Computer Networking mentioning
confidence: 99%
“…An alternative to [6], is the Metacognitive Awareness Inventory (MAI) scale developed by [7]. It has been used by [8] for assessing the baseline of students' metacognitive skills in a Foundations in Engineering program, helping them construct meaningful knowledge and skills. The MAI is a 52-item self-reported instrument to measure metacognitive awareness of adults.…”
Section: Introductionmentioning
confidence: 99%